2016
DOI: 10.1080/09593330.2016.1192691
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure anaerobic digestion up to 100 bar: influence of initial pressure on production kinetics and specific methane yields

Abstract: To ensure an efficient use of biogas produced by anaerobic digestion, in some cases it would be advisable to upgrade the biogenic gases and inject them into the transnational gas grids. To investigate biogas production under high-pressure conditions up to 100 bar, new pressure batch methane reactors were developed for preliminary lab-scale experiments with a mixture of grass and maize silage hydrolysate. During this investigation, the effects of different initial pressures (1, 50 and 100 bar) on pressure incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Based on the design of the two-phase AD process, Gianico et al (2015) enhanced process stabilization and improved VS removal efficiency and methane yield through sequential mesophilic/thermophilic AD. A number of researches have established pressurized AD systems to improve biogas production and purify the biogas (Chen et al, 2014;Merkle et al, 2017aMerkle et al, , 2017b. By increasing operating pressures in methane reactors, methane content could be increased up to 90.45% at 50 bar.…”
Section: Recent Development For Enhancing Resource Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the design of the two-phase AD process, Gianico et al (2015) enhanced process stabilization and improved VS removal efficiency and methane yield through sequential mesophilic/thermophilic AD. A number of researches have established pressurized AD systems to improve biogas production and purify the biogas (Chen et al, 2014;Merkle et al, 2017aMerkle et al, , 2017b. By increasing operating pressures in methane reactors, methane content could be increased up to 90.45% at 50 bar.…”
Section: Recent Development For Enhancing Resource Recoverymentioning
confidence: 99%
“…Jones and Greenfield (1982) revealed that regulating metabolic pathways through controlling headspace pressure resulted in gas dissolved in the reactor. Previous studies have reported that headspace environment including headspace pressure and partial pressure is an important factor for management of the metabolic pathways and regulating specific metabolic products on the acidogenic phase (Merkle et al, 2017a;Yan et al, 2017). Upon a decrease in hydrogen partial pressure, the hydrogen production also decreases, which consequently changes the underlying metabolic processes.…”
Section: Critical Factors Affecting Acidogenic Processmentioning
confidence: 99%
“…Several empirical studies focused on the variation in microbial composition, i.e. bacteria and archaea, dominating the process [ 22 , 39 , 40 ]. These studies highlighted the interaction between community composition, CH 4 content of the biogas and rate of biogas production.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are few studies on the effect of increased pressure on the performance of digesters [36]. Modern research is mainly focused on the use of high pressure in biogas technology to increase the calorific value of biogas and its further use in gas distribution networks [19,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%